Effects of acupuncture on the pain and function of the hands of selected patients with rheumatoid arthritis - Seca, Susana Marisa Ferraz (2020)
Tese no âmbito do doutoramento em Ciências da Saúde, no ramo Enfermagem, apresentada à Faculdade de Medicina da Universidade de Coimbra